2020
DOI: 10.1007/s12282-020-01067-2
|View full text |Cite
|
Sign up to set email alerts
|

High absolute lymphocyte counts are associated with longer overall survival in patients with metastatic breast cancer treated with eribulin—but not with treatment of physician’s choice—in the EMBRACE study

Abstract: Background Eribulin, a nontaxane synthetic inhibitor of microtubule dynamics, is widely used to manage locally advanced or metastatic breast cancer (MBC). Eribulin has demonstrated immunomodulatory activity on the tumour microenvironment. Baseline neutrophil-to-lymphocyte ratio (NLR), a marker of immune status, may predict progression-free survival in eribulin treatment. This post hoc analysis assessed predictors for overall survival (OS). Methods The phase 3 open-label study (EMBRACE) of eribulin versus treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 19 publications
(28 reference statements)
7
95
1
Order By: Relevance
“…Recent studies have highlighted the crucial role of tumor microenvironment in the tumor progression and treatment response 5 . Furthermore, reports suggest subcategorization of white blood cells or platelets and their functions associated with tumor progression or suppression 6 8 . Numerous studies have confirmed the clinical significance of the neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) in HCC 9 12 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have highlighted the crucial role of tumor microenvironment in the tumor progression and treatment response 5 . Furthermore, reports suggest subcategorization of white blood cells or platelets and their functions associated with tumor progression or suppression 6 8 . Numerous studies have confirmed the clinical significance of the neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) in HCC 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the prognostic significance and/or actual role of each blood cell in various tumors and/or the clinical significance of the absolute blood cell count itself have been investigated 6 8 , 14 . The analysis from these studies considered absolute blood cell counts rather than the ratio of these cells to understand the mechanism of how each cell type regulates progression and/or suppression in tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a low baseline ALC is strongly associated with reduced disease-free survival (DFS) (hazard ratio [HR] 5.24, 95% CI 2.23-12.30, P < 0.001) and OS (HR 6.13, 95% CI 2.21-17.0, P < 0.001) for patients with breast cancer who undergo primary chemotherapy 11,14 . High ALC (≥ 1000/ μL or 1500/µL) was identified as an independent predictive marker for better OS in patients with ABC receiving eribulin therapy 19,20 . In a previous meta-analysis of patients with unselected solid tumors, high NLR was associated with poor OS (HR 1.81, 95% CI 1.67-1.97, P < 0.001).…”
Section: Discussionmentioning
confidence: 96%
“…High absolute lymphocyte counts (ALC) have been associated with prolonged survival in patients with MBC treated with eribulin, but not TPC in patients enrolled in the EMBRACE trial. 51 OS was prolonged with eribulin vs TPC in patients with baseline ALC ≥1500/µL (HR, 0.59; 95% CI: 0.437–0.784; P<0.001). However, there was no significant difference by treatment in patients with ALC <1500/µL.…”
Section: Efficacy Of Eribulin In Specific Breast Cancer Subtypesmentioning
confidence: 99%